2017
DOI: 10.5851/kosfa.2017.37.2.297
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microbial and Radioactive Contaminations in Korean Cold Duck Meats and Electron-Beam Application for Quality Improvement

Abstract: Animal-origin food products pose serious threat to public food safety due to high microbial loads. The microbial and radioactive contaminations in commercial cold duck meat products were evaluated. Ten different lots of commercial samples (C1-C10) were classified based on type and smoking process. All samples were highly contaminated (< 4-7 Log CFU/g) with total aerobic bacteria (TAB), yeasts and molds (Y&M), and 7 samples (C1-C7) were positive for coliforms. Furthermore, three samples were contaminated with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
5
1
1
Order By: Relevance
“…In contrast to the results of the current study, low coliform counts in beef cattle (5.29X10 1 cfu/g) was found [27]. However, higher contamination rates within Korean cold duck meats with total aerobic bacterial count of 4-7 log cfu/g and coliforms count of 3.72-5.92 cfu/g has been reported [28].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the results of the current study, low coliform counts in beef cattle (5.29X10 1 cfu/g) was found [27]. However, higher contamination rates within Korean cold duck meats with total aerobic bacterial count of 4-7 log cfu/g and coliforms count of 3.72-5.92 cfu/g has been reported [28].…”
Section: Discussioncontrasting
confidence: 99%
“…Ionizing radiation (X-ray, gamma ray, and electron beam) is well-known as an effective method for destroying spoilage and pathogenic microorganisms in foods [11]. The radiation of D10 values (dose of radiation necessary to reduce the population by 1 log 10 , or 90%) of various Salmonella strains was 0.65 kGy [12]. In addition, it was demonstrated that D10 value is depending on the isolates and substrate [13].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the worst case, that is, the D ‐value of L. innocua (0.55 kGy) to achieve 2.39 decimal reductions in the number of Listeria spp., a treatment of 1.32 kGy (2.39 D × 0.55 kGy) would be necessary to reach the FSO according to the USDA criteria. This value is lower than those recommended for fresh poultry (2.5–7 kGy) (Patterson, ; Wood & Bruhn, ), red meat (4.5 kGy) (Wood & Bruhn, ), commercial cold duck meat products (3–7 kGy) (An et al, ), and RTE bologna (3 kGy) (Sommers et al, ). This difference could be due to the higher a w of these products which favors the growth of Listeria , during their shelf life.…”
Section: Resultsmentioning
confidence: 70%
“…Electron beam (E‐beam) treatment is considered a process that can ensure that food safety standards are met without significant losses in food quality (Li & Farid, ; Pillai & Shayanfar, ; Roberts, ). Moreover, several authors have described its efficacy in reducing L. monocytogenes in various meat products, such as bologna, frankfurters, cooked pork and turkey ham (Foong, Gonzalez, & Dickson, ; Kudra et al, ), pork and beef loin (García‐Márquez, Cambero, Ordonez, & Cabeza, ; Yim, Jo, Kim, Seo, & Nam, ), duck meat (An et al, ; An, Jo, Akram, Suh, & Kwon, ), fermented sausages (Cabeza et al, ), and dry‐cured and cooked ham slices (Benedito et al, ; Cabeza et al, ; Cabeza et al, ; Cambero et al, ; Hoz, Cambero, Cabeza, Herrero, & Ordonez, ).…”
Section: Introductionmentioning
confidence: 99%